Neutrophils enhance the clearance of systemic amyloid deposits in a murine amyloidoma model - Hancock, Trevor J.; Vlasyuk, Marina; Foster, James S.; Macy, Sallie; Wooliver, Daniel C.; Balachandran, Manasi; Williams, Angela D.; Martin, Emily B.; Kennel, Stephen J.; Heidel, Eric R.; Wall, Jonathan S.; Jackson, Joseph W. (Frontiers in Immunology, 2024)
IntroductionAmyloid-specific antibodies have been shown to opsonize and enhance amyloid clearance in systemic amyloidosis mouse models. However, the immunological mechanisms by which amyloid is removed have not been clearly defined. Previous reports from preclinical in vivo studies suggest polymorphonuclear cells (i.e., neutrophils) can affect amyloid removal. Therefore, we sought to analyze how neutrophils may contribute to the clearance of human AL amyloid extracts, using a murine amyloidoma model.MethodsImmunocompromised nude mice injected subcutaneously with patient-derived AL amyloid extract (generating a localized “amyloidoma”) were used to circumvent confounding factors contributed by the adaptive immune system and served as the model system. Two representative AL amyloid extracts were used, ALλ(CLA), which is refractory to clearance, and ALκ(TAL), which is readily cleared in mice. Neutrophil recruitment to the amyloid masses, cellular activation, and propensity to engulf amyloid were assessed.ResultsImmunophenotyping of amyloidomas from animals implanted with 2 mg of either ALλ or ALκ revealed that more neutrophils were recruited to ALκ amyloid masses as compared to the ALλ material, which was generally devoid of neutrophils. Ex vivo analyses indicated neutrophils do not efficiently phagocytose amyloid directly. However, histological evaluation of the ALκ amyloidoma revealed the abundant presence of neutrophil extracellular traps, which were absent in the ALλ amyloidomas. Using neutrophil depletion experiments in mice, we determined that mice devoid of neutrophils cleared the human amyloid lesions less efficiently. Moreover, mice devoid of neutrophils also had significantly reduced intra-amyloid expression of inflammatory cytokines.DiscussionNeutrophils may not directly mediate amyloid clearance through phagocytosis; however, these cells can be stimulated by the amyloid and may function to facilitate phagocytosis and amyloid clearance by professional phagocytes (e.g., macrophages).